Transcriptome analysis of the pathogenic ciliate after hydrogen peroxide treatment - Hyunsu Kim; A-Reum Lee; Kyung-Yoon Jeon; Eun-Ji Ko; Hee-Jae Cha; Mee Sun Ock (Kosin Medical Journal, 2022)
Background The scuticociliate Miamiensis avidus is a highly pathogenic ciliate responsible for serious damage to various organs of aquaculture fish. In particular, the olive flounder aquaculture industry is suffering massive losses due to M. avidus infection. Hydrogen peroxide (H2O2) is one of the most widely used chemicals for scuticociliate treatment. Despite the superior killing effect of H2O2, studies on transcription levels and gene expression changes after H2O2 treatment are limited. We conducted an mRNA transcriptome analysis to compare the differentially expressed gene (DEG) profiles between the ciliate and cyst-like stages of M. avidus after H2O2 treatment. Methods We applied DEG profiling to identify DEGs during the ciliate and cyst-like stages of M. avidus. Results There were 5,967 DEGs among the 9,075 transcripts identified, and 50 of these DEGs were significantly different (p<0.05). Among these, 21 DEGs were upregulated and 29 were downregulated in the cyst-like stage. The most significantly upregulated genes during the change to the cyst-like stage were cytochrome c oxidase genes. Genes related to the calcium channel were also highly upregulated. Conclusion The significant upregulation of cytochrome c gene expression and cytosolic calcium ion channel-related gene expression after H2O2 treatment suggests that ciliate mortality occurred through apoptosis. The formation of the cyst-like stage is considered a temporary form during the process of apoptosis. Information on the gene expression profile of M. avidus in response to H2O2 is expected to contribute to the understanding of the mechanism of action of therapeutic agents against this pathogen.